The semiotics of authority: a closely-observed lesson. Issue 2 (3rd April 2019) - Philp, Hannah
ABSTRACT: This article looks at the ways in which the semiotics of authority are established and challenged during a secondary school English lesson on The Strange Case of Dr Jekyll and Mr Hyde . I focus on the utterances of one student and the context of the classroom in which she finds herself as a means to explore the ways in which pedagogic identities and relationships are negotiated and contested.